Nilai Sosial Tokoh dalam Novel Nyoman Sulastri Karya Gerson Poyk - Mardhiyah, Ainun; Nai, Firmina Angela; Jama, Karolus B. (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2025)
The focus of this research is adjusted to the formulation of the problem discussed in this research, namely, what are the social values ​​carried by the characters in the novel Nyoman Sulastri by Gerson Poyk. The theory used in this research is Lowenthal's theory: Social Barometer. The method used in this research is a descriptive qualitative method. Research results The results of this research show that the character Nyoman Sulastri has the value of social responsibility, the character Hanibal has the social value of cooperation, the character Sujono has the value of social responsibility, and the character Barbara has the value of social responsibility. The four figures have dominant social values ​​from each of the three social values ​​studied, namely love, responsibility and life harmony. The conclusion of this thesis is that these figures have different dominant social values, starting from responsibility towards family, work, education and cooperation. These figures can adapt to other social values ​​when they are in a place or interacting with other individuals or groups.